Metodologias diversificadas como estratégias para o ensino de micologia na educação básica - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Much of the contents addressed in the scope of the subjects of Science and Biology is not understood by the students, among them the fungi theme draws attention because its approach is marked by the mere transfer of theoretical concepts present in textbooks and their exposition consists in memorization, without appreciation. of contextualization. In this context, the present work aimed at the development and application of different methodologies, focused on contextualization, experimentation, playfulness, and active and investigative learning, involving fungi. The target audience was students from two school units of the state school system of the state of Goiás, covering classes from 6th to 9th grade of elementary school. The research presents a qualitative and quantitative approach and data collection was performed through drawings, observations of participation, involvement and faithful description of the students' statements. The first step of the research was to evaluate the efficiency of three distinct methodologies to diagnose students' prior knowledge of fungal content. The second stage was characterized by the elaboration and application of different methodologies for approaching the fungal content: Cine Fungi, Mycological Exhibition, Fungal Experiment Library, lecture and dialogues, monitored visit to FungiLab and Hands on Pasta activity. The third stage of the research aimed to evaluate the effectiveness of the activities performed and collect students' opinion about the proposal developed through the making of comic books and Papo Fungi. In the survey of the previous knowledge of the students it was found that some had relevant concepts while others had distorted and misconceptions about the fungi. Referring to the second we found in general that the students were very interested and had a good participation in the activities. At Cine Fungi the students were questioning and showed interest in studying more about the fungi. The Mycological Exhibition allowed students to know the breadth of the Fungi Kingdom through the manipulation of didactic models and the topics covered. The Fungal Experiment Library provided students with observation, hypothesis raising, research and the socialization of knowledge. In the fourth activity, although it was a lecture, the analysis of the speeches and the students' participation showed that the activity had a very positive balance. Regarding the monitored visit to FungiLab, we noticed that it was marked by the willingness and enthusiasm of the students, as they were participating in a different class from routine classes within the school. In the activity Hands on Dough we showed that the students understood more effectively the process of fermentation from a daily situation, as in the preparation of bread. We conclude that the developed work offered alternatives for the teaching of fungi, through the use of diversified strategies, which facilitated the comprehension of the content. Thus they can be substantial in the process of developing and building knowledge of learners, in order to stimulate meaningful learning, materializing the idea that this new educational trend enables teachers and students to realize an attractive and dynamic pedagogical practice with great chances of success.
Diversified methodologies as strategies for teaching mycology in basic education
Keywords: Aprendizagem Significativa; Experimentação; Fungos; Ludicidade; Meaningful Learning; Experimentation; Fungus; Playfulness; CIENCIAS BIOLOGICAS